Prevention of Salmonella Infection in Poultry by Specific Egg-Derived Antibody - Rahimi, Shaban; Shiraz, Zahra Moghadam; Salehi, Taghi Zahraei; Torshizi, Mohammad A. Karimi; Grimes, Jesse L. (International Journal of Poultry Science, 2007)
Salmonella enteritidis (SE) colonizes the intestinal tract of poultry and causes food born illness in humans. Reduction of (SE) colonization in the intestinal tract of poultry reduces potential carcass contamination during slaughter. The purpose of this study was to investigate the effect of SE-specific yolk immunoglobulin (IgY) on prevention of SE colonization in orally infected broiler chickens. Commercial Single Comb White Leghorn (SCWL) hens were hyperimmunized with SE whole cell antigens. The presence of anti-Salmonella antibody, IgY and IgG in egg yolk and serum respectively, was monitored by Enzyme Linked Sorbent Assay (ELISA). Two hundred forty male `Ross 308` day old chicks were randomly assigned to 8 groups and 3 replications of 10 birds were grown for 42 days of experiment. Eight experimental groups identified with, S, P, A, SP, SA, AP, SPA, C. Four birds from four challenged groups (S), were orally inoculated with 1 mL of bacterial suspension that contained 1×106 CFU mL-1 S. enteritidis at 3 day of age. The groups that supplemented with antibody (A) received 15 mL of yolk contained antibody mixed per 3.84 mL of drinking water on day 1 and continuing for duration of the experiment. The probiotic treated groups (P) were received probiotic, 0.1% of feed and 0.5% of feed, until day 21 and 56 respectively. One group as control (C) did not received any treatment of probiotic and antibody. A-treated and A-P treated groups had significantly lower fecal shedding (p<0.01) and lower concentration of SE cecal colonization (p<0.01). These groups also had a lower isolation of SE from the liver, spleen and ileum. The use of Salmonella enteritidis-specific IgY combined with probiotic had a beneficial effect in reducing the colonization of Salmonella in market-aged broiler under the condition of this study.